The Teaching-Learning Nexus: Supporting and Preparing Students for Their Role as Medical Radiation Technologists - Thompson, Andrea Jane (Auckland University of Technology, 2013)
A curriculum comprising a significant academic and clinical component is designed to prepare medical radiation technology (MRT) students for their role as medical radiation technologists. Importantly, the academic and clinical components are integrated to achieve this goal, however, it can be demanding for the students who need to meet numerous educational requirements and expectations within a three- year period. It is essential, therefore, to develop a more holistic understanding of the educational experience for the students and to establish how their learning is supported so that teaching and learning processes can be fostered and improved. This action research study was structured in two phases. Phase One uncovered something of the learning experiences of MRT students. Phase Two instigated a learning partnership initiative to improve support for learning for medical imaging students in the clinical setting. Two key developments, which emerged during the action research process, included the introduction of an online platform to augment the learning partnership and personal digital assistants (PDAs) for students to collect evidence of their clinical learning. In order to understand the learning experiences of students, data were gathered in Phase One through focus groups with MRTs and students, observations of student/teacher encounters in the clinical and educational settings and interviews with MRT and clinical tutor participants. Data were generated in Phase Two by a series of collaborative action research meetings with students and MRT participants during the development of the learning partnership initiative. The collection of data and analyses were mutually intertwined and the participants’ contribution played a key role in the production of knowledge. A robust relationship between a student and their MRT partner, fostered the development of the student’s confidence and competence, gave them a sense of belonging and encouraged them to explore and question aspects of practice to progress their learning. The relationship was not uni-directional as it also supported the enhancement of MRTs’ practice. Within the teaching-learning nexus, setting of goals, engagement in a cognitive apprenticeship, and the impact of technology were important dimensions identified for teaching and learning. The findings of this thesis have revealed tensions for teaching and learning for MRTs, students and clinical tutors. Ineffective supervision and disparities in teaching between the groups involved in the facilitation of learning were key tensions identified. The disparities were mostly influenced by MRTs, students and clinical tutors prioritising types of knowledge differently. The learning partnership initiative provided a new way to support teaching and learning in the clinical setting. However, the recommendations from the study suggest the need for curriculum revision that redefines knowledge for practice and assessment requirements. A key aim should be to enable MRTs, students and clinical tutors to have a similar understanding of the expectations and requirements for practice. MRTs need to be better supported in their teaching role to enable them to make a greater investment in students’ learning. In addition, a redistribution of funding for clinical education needs to be considered to support the MRTs’ central role in teaching medical imaging students.
Keywords: Medical radiation technology; Action research; Technology for clinical learning; Knowledge for practice; Bourdieu; Cognitive apprenticeship